25. EVALUATE EFFECTS OF “BAN HA BACH TRUAT THIEN MA THANG” REMEDIES COMBINED WITH EAR ACUPUNCTURE IN THE TREATMENT OF VESTIBULAR DISORDERS (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate effects of “Ban ha bach truat thien ma thang” remedies combined with ear acupuncture in the treatment of vestibular disorders with phlegm rheum.Research methods: Using prospective method, controlled open clinical intervention and comparison before and after treatment.Results: After 20 days of treatment, “Ban ha bach truat thien ma thang” remedies combined with ear acupuncture has a good effect in the treatment of vestibular disorders with phlegm rheum, specifically on the EEV, VAS, Pittsburgh scores. Reducing symptoms of dizziness and vertigo through improving EEV score better than the control group from 12.27 ± 1.55 points to 4.07 ± 1.76 points with p < 0.05. Reducing headache symptoms through improving VAS scores from 4.67 ± 0.84 points to 1.13 ± 1.07 points compared to the control group with p < 0.05, statistically significant difference. Improved sleep quality better than the control group through reduced performance scores from 12.37 ± 2.3 points to 5.97 ± 1.67 points with p < 0.05, statistically significant difference.Conclusion: The medicine “Ban ha bach truat thien ma thang” combined with ear acupuncture is effective in treating low phlegmon vestibular dysfunction.
Keywords: “Ban ha bach truat thien ma thang”, ear acupuncture, vestibular disorders.